The Soviet Union and the arms race - David Holloway (Yale Univ, 1984)
The book examines a number of specific questions about the Soviet Union's role in the nuclear arms race. It deals with the influence of international military rivalry, and of the Soviet efforts to build up the Red Army, the formation of the Soviet state; Soviet thinking about nuclear war and the uses of military force in the nuclear age; and the economic and political institutions that sustain the military effort